Antimalarial, Antioxidant, and Toxicological Evaluation of Extracts of Celtis africana, Grosseria vignei, Physalis micrantha, and Stachytarpheta angustifolia - Michael Konney Laryea; Lawrence Sheringham Borquaye (Biochemistry Research International)
In many parts of the world, malaria undoubtedly poses a serious threat to health care systems. Malaria treatment has increasingly become complicated, primarily due to the emergence of widespread resistance of the malaria parasites to cheap and affordable malaria therapeutics. The use of herbal remedies to treat various ailments, including malaria and malaria-like ailments in Ghana is common. We herein report on the antiplasmodial and antioxidant activities as well as toxicological evaluation of four medicinal plants (Celtis africana, Grosseria vignei, Physalis micrantha, and Stachytarpheta angustifolia) commonly used to treat malaria in Ghana. Following Soxhlet extraction of plant samples in ethanol, extracts were screened against Plasmodium falciparum (3D7 strain) in an in vitro antiplasmodial assay. The phosphomolybdenum and DPPH (1, 1-diphenyl-2 picrylhydrazyl) assays were used to evaluate antioxidant activities while toxicity assessment was carried out in mice using the acute toxicity test and kidney and liver function tests. Extracts from Celtis africana and Physalis micrantha were very active towards the parasites with half-maximal inhibitory concentrations (IC50’s) of 29.1 and 3.5 µg/mL, respectively. Extracts of Grosseria vignei and Stachytarpheta angustifolia were inactive, having IC50 values greater than 50 µg/mL. All extracts exhibited excellent total antioxidant capacities (>800 mg/g AAE) and good DPPH radical scavenging potential (IC50 range of 300–900 µg/mL). The median lethal dose (LD50) of all extracts in the toxicological evaluation was greater than 2000 mg/kg and there was no effect of extracts on the levels and activities of key biomarkers of liver and kidney function. The activities of these plants obtained in this study partly give credence to their folkloric use in herbal medicines and suggest that they could provide promising lead compounds for malaria drug discovery programs.